Radiation-induced effects and the immune system in cancer - Kaur, Punit; Asea, Alexzander (Frontiers in Oncology, 2012)
Chemotherapy and radiation therapy (RT) are standard therapeutic modalities for patients with cancers, and could induce various tumor cell death modalities, releasing tumor-derived antigens as well as danger signals that could either be captured for triggering anti-tumor immune response. Historic studies examining tissue and cellular responses to RT have predominantly focused on damage caused to proliferating malignant cells leading to their death. However, there is increasing evidence that RT also leads to significant alterations in the tumor microenvironment, particularly with respect to effects on immune cells and infiltrating tumors. This review will focus on immunologic consequences of RT and discuss the therapeutic reprogramming of immune responses in tumors and how it regulates efficacy and durability to RT.